Visualizing elements of order $7$ in the Tate–Shafarevich group of an elliptic curve. Issue Volume 19:Issue A(2016) (August 2016) - Fisher, Tom
Abstract : We study the elliptic curves in Cremona's tables that are predicted by the Birch–Swinnerton-Dyer conjecture to have elements of order $7$ in their Tate–Shafarevich group. We show that in many cases these elements are visible in an abelian surface or abelian 3-fold.